EFL Teaching Strategies in Multilingual Classrooms: A Case Study of Universitas Muhammadiyah Surakarta (UMS) - Sabir, Muhammad Rehan; Mansoor, Hafiza Sana; Candraningrum, Dewi (Forum for Linguistic Studies, 2025)
This research investigates the teaching strategies employed by English as a Foreign Language (EFL) lecturers, using Universitas Muhammadiyah Surakarta (UMS) as a case study. The qualitative case study examines how EFL lecturers manage multilingual classroom realities. These classrooms include native speakers of Javanese, Bahasa Indonesia, and various international first languages. Data were gathered through six classroom observations, three semi-structured interviews, and two focus group discussions with students (N = 12). Reflexive thematic analysis revealed four themes: (1) gaps in participation due to differences in proficiency and fear of making mistakes; (2) strategic use of L1 for clarification, vocabulary support, and reducing anxiety; (3) multimodal scaffolding involving images, peer tutoring, and task-oriented work; and (4) policy negotiation, with phased L1 decrease in high-stakes testing. The study draws primarily on sociocultural theory and translanguaging, with interlanguage providing supplementary insights into the development of learner language. This study extends translanguaging and sociocultural theories by introducing negotiated translanguaging—showing how multilingual practices adapt strategically under EMI policy constraints in higher education contexts. The significance of this research lies in addressing the growing challenge of dealing with multilingual classrooms in Indonesian higher education. Linguistically diverse backgrounds frequently restrict learner participation and understanding. The findings support an adaptable language policy. They also stress training and evaluation in multilingual pedagogy aligned with classroom contexts. This study gives practical recommendations to lecturers, managers, and policymakers working in linguistically diverse higher education institutions.